Development of Personal Knowledge Management System with Learning Contract and Peer Assisted Learning for Enhance Academic Work of Graduate Students - Hongsrichinda, Cherdwong; Na-songkhla, Jaitip; Natakuatoong, Onjaree (Scholar: Human Sciences, 2016)
The purpose of this study was development of personal knowledge management system using learning contract and peer-assisted learning to enhance academic task of graduate students. The research and development (R&D) process was divided into four phases: 1) studied, analyzed and synthesized related documents and interviewed the experts’ opinions concerning components and steps of personnel knowledge management process, learning contract process and peerassisted learning process 2) developed a prototype of personnel knowledge management system for learning communities using learning contract and peerassisted learning 3) studied the effects of the system for six weeks and 4) proposed the personnel knowledge management system using learning contract and peerassisted learning. The instruments used in this research consisted of document management system, blog system, rubric for academic writing, a product evaluation form, and an after action review form. The populations of this experiment were graduate students of Department of Education Technology Faculty of Education Chulalongkorn University, who enrolled the course of Research in Educational Technology and Communications. Quantitative statistics used in this study were frequency distributions, percentage, mean, standard deviation and Wilcoxon Matching Pairs Signed-Ranks Test. The research findings indicated that: 1. The developed process composed of three components: 1) people including graduate student teacher and peer as experienced student 2) learning contract and 3) technology for personal knowledge management. 2. The developed process composed of four steps: 1) preparation 2) process 3) presentation and 4) evaluation. 3. There were significant differences between pretest and posttest personnel knowledge skill scoring at the .05 level. The overall academic works developed by the samples were evaluated at a good level.